Catalytic pyrolysis of empty fruit bunch (EFB) using metal oxide based catalysis - Alina Rahayu Mohamed (School of Bioprocess Engineering, University Malaysia Perlis, 2015)
This research focused on the utilization of values of activation energy (Ea) estimated from non-catalytic and catalytic thermogravimetric prolysis of EFB with a series of metal oxide as a measuring tool to select the respective metal oxide catalyst for incorporation with the reactor study.